Análise de comportamento estrutural de juntas soldadas dissimilares off-shore: influência do hidrogênio na tenacidade - Alves, Daniel Nicolau Lima (2024)
In the face of a context of growing energy demand in recent years, substantial offshore upstream operations (exploration, drilling, and production) have been fostered, with a focus on the pre-salt oil modality. The construction of productive systems in the underwater environment requires a cathodic protection system (CP) in order to prevent the corrosion process. Such structures have shown brittle fractures in regions of dissimilar welded joints (DWJ) over the years, and these failures have been associated with the presence of hydrogen due to the CP system. This reveals the need for further investigations regarding the suscetibility of the material used to the hydrogen-rich environment, as well as greater clarity on the phenomenon of hydrogen embrittlement. The type of DWJ to be analyzed is applied in joining flanges to pipes present in offshore production lines, and it has been shown to be suscetible to hydrogen embrittlement when kept under a cathodic protection system with occurrences of failures in the interface region of the buttering of the base metal (BM) with the Inconel 625 nickel alloy. This work aims to analyze the influence of the hydrogenation cycle on the structural behavior of the dissimilar welded joint ASTM A182 F22/INCONEL625/ASTM A36, through the analysis of the Hydrogen Embrittlement Index associated with parameters such as elongation, reduction of area, and toughness. Among the contributions presented are: the proposal of an energetic approach for the Hydrogen Embrittlement Index (HEI); suscetibility to hydrogen embrittlement at different periods (7 and 21 days) of exposure to cathodic protection loads; and the trend curve of hydrogen embrittlement versus hydrogenation cycle regarding the analyzed dissimilar joint. For the construction of the DWJ, the buttering technique was applied using the Gas Metal Arc Welding (GMAW) conventional process, which was also employed for the union of the JSD. The hydrogenation process was carried out using a 3.5% NaCl aqueous solution at a potential of -1,100 mVERC at room temperature. The influence of hydrogen was analyzed through tensile testing and Hydrogen Embrittlement Indices. The parameters analyzed in this study were IFH-A (elongation), IFH-E (reduction of area), and IFH-T (toughness). Microstructural analysis was performed using optical and scanning electron microscopy, as well as fractography analysis. The hydrogenated samples revealed significant suscetibility to hydrogen embrittlement. However, the IFH-A and IFH-E indices, for comparative purposes, were not suitable for analyzing samples consisting of bimetallic materials - metallurgically dissimilar. The IFH-T was proposed as a parameter for comparing hydrogen embrittlement of dissimilar metal welded joints (JSD), indicating an additional average embrittlement of 93.72% in the hydrogenated samples. Finally, the results indicate a clear tendency of increased hydrogen embrittlement and, consequently, a reduction in toughness as the exposure cycles to hydrogen progress. The hydrogenated samples showed significantly brittle fracture mechanisms - quasi-cleavage - when compared to non-hydrogenated samples, which exhibited predominantly microcavity coalescence (dimples) mechanisms on their fracture surfaces.